Association of angiotensinogen and angiotensin II receptor type I polymorphisms with biomarkers of carbohydrate and lipid metabolism in Dagestan residents with type 2 diabetes and hypertension - M. Z. Saidov; S. N. Mammaev; G. M. Magadova; R. M. Balamirzoeva; Z. Sh. Magomedova; Z. S. Magomedova; A. U. Gamzaeva (Российский кардиологический журнал, 2021)
Aim. To study the associations of angiotensinogen (AGT) (s4762(С521Т), rs699(Т704C)) and angiotensin II receptor type I (AGTR1) (rs5186(A1166C)) genetic polymorphisms with serum levels of insulin, glucagon, C-peptide, leptin, as well as with dyslipidemia and glycemic levels in Dagestan residents with combination of type 2 diabetes (T2D) and hypertension (HTN), as well as with isolated T2D/HTN.Material and methods. We examined 16 patients with isolated T2D, 59 patients with T2D+HTN and 51 patients with isolated HTN from Dagestan. Genetic polymorphisms of the AGT and AGTR1 genes were studied. The levels of insulin, glucagon, C-peptide, and leptin were studied by enzyme-linked immunosorbent assay (ELISA), while lipid and carbohydrate metabolism — by biochemical methods.Results. In patients with T2D, the association of CC genotype of AGT gene rs4762(С521Т) polymorphism with a leptin decrease was determined, while its CT genotype was associated with an increase in serum level of triglycerides. The TC genotype of AGT gene rs699(Т704C) polymorphism was associated with an increase in leptin, triglyceride and glucose levels. The AA genotype of AGTR1 gene rs5186(A1166C) polymorphism was associated with an increase in insulin and glucose levels, as well as a decrease in leptin level. In patients with a combination of T2D and HTN, CC and CT genotypes of AGT gene rs4762(С521Т) polymorphism was associated with a decrease in glucagon level. The TT genotype of AGT gene rs699(Т704C) polymorphism was associated with an increase in insulin, triglyceride, glucose and body mass index (BMI) levels. In isolated HTN, the CC and CT genotypes of AGT gene rs4762(С521Т) polymorphism were associated ith a decrease in glucagon level. The TT genotype of AGT gene rs699(Т704C) polymorphism was associated with increased levels of insulin, low density lipoproteins, and BMI.Conclusion. Associations of AGT (s4762(С521Т), rs699(Т704C)) and AGTR1 (rs5186(A1166C)) genetic polymorphisms with carbohydrate and lipid metabolism changes are an important pathogenetic link of T2D and HTN, which allows developing an individual prognosis of these diseases in Dagestan residents.